Post-introduction economic evaluation of pneumococcal conjugate vaccination in Ecuador, Honduras, and Paraguay - Dagna O. Constenla
OBJECTIVE:A decision-analytic model was constructed to evaluate the economic impact of post-introduction pneumococcal conjugate vaccine (PCV) programs in Ecuador, Honduras, and Paraguay from the societal perspective. METHODS: Hypothetical birth cohorts were followed for a 20-year period in each country. Estimates of disease burden, vaccine effectiveness, and health care costs were derived from primary and secondary data sources. Costs were expressed in 2014 US$. Sensitivity analyses were performed to assess the impact of model input uncertainties. RESULTS: Over the 20 years of vaccine program implementation, the health care costs per case ranged from US$ 764 854 to more than US$ 1 million. Vaccination prevented more than 50% of pneumococcal cases and deaths per country. At a cost of US$ 16 per dose, the cost per disability-adjusted life year (DALY) averted for the 10-valent PCV (PCV10) and the 13-valet PCV (PCV13) ranged from US$ 796 (Honduras) to US$ 1 340 (Ecuador) and from US$ 691 (Honduras) to US$ 1 166 (Ecuador) respectively. At a reduced price (US$ 7 per dose), the cost per DALY averted ranged from US$ 327 (Honduras) to US$ 528 (Ecuador) and from US$ 281 (Honduras) to US$ 456 (Ecuador) for PCV10 and PCV13 respectively. Several model parameters influenced the results of the analysis, including vaccine price, vaccine efficacy, disease incidence, and costs. CONCLUSIONS: The economic impact of post-introduction PCV needs to be assessed in a context of uncertainty regarding changing antibiotic resistance, herd and serotype replacement effects, differential vaccine prices, and government budget constraints.